”Where Are You Really From?”: “Mapping” the South Asian Diasporic Through Poetic Inquiry (LEARNing Landscapes, 2022)
For the South Asian diasporic, questions about (be)longing and identity are almost undeniable. Through a personal reflection, I contour these experiences by way of poetic inquiry, specifically interrogating “performing” Canadian-ness (Alvi, 2020) and the meaning of “home” (Badruddoja, 2006) that are a part of the living pedagogy of immigrant families navigating the “status“ of emigration. It is in that intermediary of “straddling cultural divide” (Sharrif, 2008) that words of poetry emerge, tantalizing a processual capitulation of (be)longing and identity formation; that is, the constant trail of navigating the in-between of “here nor there” and the (im)possibilities that this hyphenation offers.
Keywords: belonging; diaspora; home; identity; South Asian; South Asian Diasporic